2017
DOI: 10.5468/ogs.2017.60.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Association of citalopram with congenital anomalies: A meta-analysis

Abstract: ObjectiveThe antenatal use of citalopram, a widely prescribed selective serotonin reuptake inhibitor, has been suspected to be associated with congenital, particularly cardiac, anomalies. This study aimed to prove the association between citalopram use and congenital anomalies.MethodsWe searched the English literature from July 1998 to July 2015, by using the search terms ‘ citalopram’, ‘ pregnancy’, ‘ birth defects’, ‘ congenital anomalies’, and ‘ malformations’ in PubMed, Embase, Web of Science, and the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
4
1
1
Order By: Relevance
“…The observed increase in MCAs and CHD with maternal use of citalopram during the first trimester was inconsistent with all previous meta-analyses [ 11 , 12 , 14 , 15 ]. A recent meta-analysis by Kang and colleagues [ 11 ], including five cohort studies and one case-control study, reported no significant associations between exposure to citalopram and the risk of CHD during pregnancy. However, over twofold cohort studies were eligible for inclusion in our analysis.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…The observed increase in MCAs and CHD with maternal use of citalopram during the first trimester was inconsistent with all previous meta-analyses [ 11 , 12 , 14 , 15 ]. A recent meta-analysis by Kang and colleagues [ 11 ], including five cohort studies and one case-control study, reported no significant associations between exposure to citalopram and the risk of CHD during pregnancy. However, over twofold cohort studies were eligible for inclusion in our analysis.…”
Section: Discussioncontrasting
confidence: 98%
“…Furthermore, none of these meta-analyses attempted to comprehensively investigate the associations between the use of SSRIs and individual SSRIs and the risks of specific congenital malformations. Some of the previous meta-analyses [ 11 23 ] examined the risks of certain congenital malformations [overall major congenital anomalies (MCAs) and cardiac malformations] with maternal use of SSRIs and/or individual SSRIs. Other meta-analyses [ 24 28 ] examined the risks of specific (cardiac) malformations with the use of only one or two specific SSRIs.…”
Section: Introductionmentioning
confidence: 99%
“…Telmisartan was taken concomitantly with citalopram. From previous studies, therapeutic use of citalopram is not associated with major birth defects 13 .…”
Section: Discussionmentioning
confidence: 91%
“…We found 17 meta-analyses about the risk of MM or cardiac malformations (CM) after exposure to SSRI ( Table 1 ). The vast majority of them did not control for possible confounding by indication as follows: 8 meta-analyses evaluated MM risk, 5 of which resulted in significant risk [ 13 , 14 , 15 , 16 , 17 ] and 3 in non-significant risk [ 18 , 19 , 20 ]; 18 meta-analyses evaluated CM risk, 11 of which report significant risk [ 13 , 16 , 17 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], while 7 report non-significant CM risk [ 14 , 15 , 20 , 23 , 24 , 28 , 29 ]. Looking for meta-analyses that accounted for possible confounding by indication, we found only two studies [ 17 , 24 ], both of which resulted in a non-significant risk for congenital malformations overall.…”
Section: Resultsmentioning
confidence: 99%